The Lexical Limits of Literary Translation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the lexical limits of literary translation, focusing on how translators negotiate untranslatable elements such as idiomatic expressions, invented language, and culturally saturated terms within canonical English texts. While existing scholarship has addressed cultural and structural challenges in translation, lexical constraints remain underexplored as an independent domain. Employing a qualitative, comparative methodology, the study analyzes passages from works by Shakespeare, Eliot, Joyce, Orwell, Woolf, and Faulkner, comparing their original English forms with French, Spanish, and German translations. Findings indicate that interpretative translation and paraphrasing most effectively preserve semantic integrity and stylistic nuance, whereas literal translation and omission frequently result in lexical distortion and cultural loss. These outcomes reinforce theoretical frameworks from Lefevere, Berman, and Nida, and highlight the need for more context-sensitive, adaptive translation strategies. The study’s implications extend to translation pedagogy, literary criticism, and digital tool development. Further research is recommended to build computational models and conduct reception studies that measure the cognitive and aesthetic impact of lexical strategies on diverse readerships.